Export manufacture competitiveness and commodity dependence: An empirical analysis of the Dutch Disease on Argentina and Chile during the commodity price boom - Santiago Gra\~na-Colella; Ignacio Silva Neira (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2024)
Extensive economic literature has covered the effect of a natural resource boom on the performance of the manufacturing sector. Specifically, the Dutch Disease hypothesis establishes that increases in commodity prices should lead to a decrease in manufacturing exports, due to significant inflows of foreign currency that subsequently appreciate the real exchange rate. In 2003, a substantial increase in commodity prices, coupled with a pronounced appreciation of the real exchange rate, triggered a process of export primarization in Latin American countries. The paper aims to empirically assess whether the Dutch Disease framework can provide a suitable explanation for this phenomenon in Argentina and Chile. Despite both countries heavily depending on natural resources, they exhibit notable differences in economic scale, composition, and evolution of manufacturing exports, as well as their economic policy approaches throughout the designated period. This task is performed through the estimation of one VAR model for each country (2003-2019). The main results indicate that while there is insufficient evidence to assert that Argentina suffered from the Dutch Disease, the evidence for Chile remains inconclusive. These divergent results could potentially find clarification in an examination of disparities in export composition and integrated technology and thereby suggest a broader analysis regarding the policy implications.
Keywords: C32; E12; F31; F41; 330; Dutch Disease; VAR models; Argentina; Chile; manufacture export; commodity price boom